(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
In this study, the acid attack test is performed on the fiber reinforced concrete incorporating with manufactured sand silica fume and coconut shell. The grade of concrete is M50. Silica fume is partially replaced with 10 % by the weight of cement and manufactured sand is partially replaced with 40% by the weight of sand. The coconut shell is partially replaced for coarse aggregate by 20%. Additionally three types of fibers are used such as steel fiber, sisal fiber, and coir fiber. The volume fraction of fibers ranges from 0 to 3%.Â The aim of this study is to evaluate the acid resistance of the fiber reinforced high performance concrete. From the experimental investigation, it was found that there is improvement in acid resistance for fiber reinforced high performance concrete when compared to plain cement concrete. Also fiber reinforced concrete improves the cracking resistance compared to plain cement concrete.